Government's Law Strategy in Dealing With Global Recession Turmoil 2023 to Strengthen Society's Economy - Mukidi, Mukidi; Purba, Nelvitia; Nurasiah, Nurasiah; Muhlizar, Muhlizar; Binti Seli, Noor Zainee (SASI, 2024)
Introduction: The threat of a global economic recession in 2023 has been a topic of discussion lately. Various forms of trade both domestically and abroad are predicted to experience a decline. Of the potential economic threats that can occur due to two factors, both external and internal.Purposes of the Research:  This study aims to analyze the Government’s law strategy in dealing with global recession turmoil 2023 to strengthen society’s economy in Indonesia.Methods of the Research: To analyze the problems in this article, the author uses empirical legal research types and then analyzes them with descriptive-analytic methods and uses a statutory approach related to the case approach as well as a philosophical, sociological approach. and juridical.Results of the Research: Facing these alarming global conditions, the Government of Indonesia has taken concrete steps, including by issuing Government Regulation in Lieu of Law Number 2 of 2022 Concerning Job Creation (Perpu Cipta Kerja), which was promulgated on December 30, 2022, LN. 2022/No.238, TLN No.6841. The Job Creation Perpu contains content material that is loaded with the interests of the Indonesian state and people and in optimizing public services there is no violation of the law or the constitution, for the steps taken by the President. Our legal system has also regulated further procedures after the Perpu is promulgated, through the legal mechanisms and procedures that apply in parliament. It is time for us to see phenomena based on real facts and data clearly, based on academic logic. Not just an analysis without facts and different origins.